De l’Anjou à la Bohême : le double portrait équestre de Pierre de Rohan-Gié - Jeanne Alis (Les Cahiers de l'École du Louvre)
In the nineteenth century, Sychrov Castle in North Bohemia became the fiefdom of a branch of the Rohan family. The windows of the residence still display a double equestrian portrait of Pierre de Rohan (1451–1513) commissioned by one of his descendants, Prince Camille de Rohan (1800–1892). The presence of these artistic models is a precious testimony to the family history, as they come from works that adorned the Château du Verger at the very end of the Middle Ages and disappeared in the eighteenth century, a hundred years before they were reused at Sychrov. This article looks back at the design of the stained-glass window and traces the origins of the artistic model used to tell the story of a vanished object through its successive copies.